The evolution of concepts of color vision - Lee, Barry. B. (2008)
The evolution of ideas about the way we see color was closely linked to physical theories of light. Proponents of both corpuscular and wave theories viewed light as a continuous spectrum. This was not easily reconciled with the fact that, for the human eye, all colors can be matched by mixture of three primaries. Physicists such as Mayer who described trichromatic color matching often assumed that there were just three types of rays in the spectrum. This argument was finally resolved by Thomas Young, who noted that trichromatic color matching was consistent with a continuous spectrum if there were just three receptors in the eye. This kind of conceptual mistake, in this case the confusion of the properties of the visual system with physical properties of light, has been common in the history of color science. As another example, the idea of trichromacy was disputed by those who viewed color sensations as opponent processes, red-green, blue-yellow and black-white. The discovery of color-opponent neurons in the visual pathway has partly resolved this dilemma. Much of the physiological substrate of the way we detect and distinguish colors is now established, but the link between the signals leaving the retina and the way we name and order colors is still poorly defined.